Imperial to international: a history of St. John's Cathedral, Hong Kong - Wolfendale, Stuart (Sheng Kung Hui: historical studies of Anglican Christianity in China, 2013)
Founded in 1849, St John's Cathedral is the oldest, neo-gothic cathedral in East Asia and China's oldest surviving, still-operating Anglican church. In its early decades, the cathedral was the center of Hong Kong colonial life. Today, it has drawn in other Hong Kong communities, becoming a truly international church with services in several languages. This first comprehensive history of St John's traces the cathedral's role as a colonial parish church and as a bishop's seat for a diocese stretching across China and beyond. It also discusses St John's significance as a center of modern worship